2021
DOI: 10.1002/smsc.202100055
|View full text |Cite
|
Sign up to set email alerts
|

Cryo‐Electron Microscopy for Unveiling the Sensitive Battery Materials

Abstract: Deep chemical and structural investigation of battery components is increasingly imperative for exploring new electrode materials and their performance iterations for the next‐generation of energy storage devices with high energy density. This is particularly true in the research realm of lithium (Li) metal and its derivatives for the robust anode. Conventionally, both Li metal and its solid electrolyte interphase (SEI) layer are chemically reactive and sensitive to electron‐beam irradiation, making the high‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 127 publications
(218 reference statements)
2
28
0
Order By: Relevance
“…In addition, advanced characterization techniques, such as cryo-TEM, have been employed to detect the SEI nanostructure of Li deposits. Consistent with the SEM observation, the cryo-TEM results showed that spherical Li formed with the assistance of the NC coating (Figure g). The fast Fourier transform (FFT) image (inset of Figure h) confirmed that the main components were Li metal and Li 2 O.…”
supporting
confidence: 55%
“…In addition, advanced characterization techniques, such as cryo-TEM, have been employed to detect the SEI nanostructure of Li deposits. Consistent with the SEM observation, the cryo-TEM results showed that spherical Li formed with the assistance of the NC coating (Figure g). The fast Fourier transform (FFT) image (inset of Figure h) confirmed that the main components were Li metal and Li 2 O.…”
supporting
confidence: 55%
“…In situ cryo-EM is not yet a reality, nonetheless ex situ cryo-EM is proving very powerful when sample preparation is performed carefully. 224,225 Further visualization of the chemical and structure information at the nanoscale should be performed. Should in situ TEM of LSBs with liquid electrolytes never be a reality, cryo-EM may well fill the gap in knowledge.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…The desired SEI should possess electron insulation, high lithium ions diffusivity, superior mechanical modulus, favorable elasticity, and homogeneous composition to inhibit the growth of treelike lithium dendrites and maintain the controllable interface stability upon repeated cycling ( Zhenxing Wang et al, 2021 ). Many advanced characterization methods (such as cryo-electron microscopy and secondary ion mass spectrometry) have been developed to study the formation process and microstructure evolution of SEI layer during repeated cycling ( Ju et al, 2021 ; Yujing Liu et al, 2021 ). However, the in situ defective SEI layer usually suffers from inferior Li-ions diffusivity, low mechanical strength, and nonuniform composition, which make it difficult to accomplish flat and stable electroplating/stripping of metallic lithium anode ( Aslam et al, 2021 ).…”
Section: Formation Process and Mechanism Of Sei Layermentioning
confidence: 99%